The Vaccinia Virus E8R Gene Product: a Viral Membrane Protein That Is Made Early in Infection and Packaged into the Virions' Core - Doglio, Laura (American Society for Microbiology, 2002)
Vaccinia virus (VV), a member of the poxvirus family, is unique among most other DNA viruses in that both transcription and DNA replication occur in the cytoplasm of the host cell. It was recently shown by electron microscopy (EM) that soon after viral DNA synthesis is initiated in HeLa cells, the replication sites become enwrapped by the membrane of the endoplasmic reticulum (ER). In the same study, a novel VV membrane protein, the E8R gene product, that may play a role in the ER wrapping process was identified (N. Tolonen, L. Doglio, S. Schleich, and J. Krijnse Locker, Mol. Biol. Cell 12:2031-2046, 2001). In the present study, the gene product of E8R was characterized both biochemically and morphologically. We show that E8R is made predominantly early in infection but is packaged into the virion. On two-dimensional gel electrophoresis, the protein appeared as a single spot throughout the VV life cycle; however, in the assembled virion, the protein underwent several modifications which resulted in a change in its molecular weight and its isoelectric point. EM of labeled cryosections of infected HeLa cells showed that the protein localized to the ER and to membranes located on one side of the Golgi complex as early as 1 h postinfection. Late in infection, E8R was additionally associated with membranes of immature virions and with intracellular mature viruses. Although E8R is predominantly associated with membranes, we show that the protein is associated with viral cores; the protein is present in cores made with NP-40-dithiothreitol as well as in incoming cores, the result of the viral entry process, early in infection. Finally, we show that E8R can be phosphorylated in vitro by the viral kinase F10L. It is able to bind DNA in vitro, and this binding may be modulated by phosphorylation by F10L. A putative role of the E8R gene product throughout the VV life cycle is discussed.